The relation between progressive osteoarthritis of the knee and long term progression of osteoarthritis of the hand, hip, and lumbar spine. Issue 5 (11th October 2005) - Hassett, G; Hart, D J; Doyle, D V; March, L; Spector, T D
Abstract : Background: The association between progression of knee osteoarthritis and progression of osteoarthritis at sites distant from the knee is unclear because of a lack of multisite longitudinal progression data. Objective: To examine the association between radiological progression of knee osteoarthritis and osteoarthritis of the hands, hips, and lumbar spine in a population based cohort. Methods: 914 women had knee x rays taken 10 years apart, which were read for the presence of osteophytes and joint space narrowing (JSN). Progression status was available for hand, hip, and lumbar spine x rays over the same 8 to 10 year period. The association between progression of knee osteoarthritis and osteoarthritis at other sites was analysed using odds ratios (OR) and 95% confidence intervals (CI) in logistic regression models. Results: 89 of 133 women had progression of knee osteoarthritis based on osteophytes, and 51 of 148 based on JSN definition. Progression of JSN in the knee was predicted by progression in lumbar spine disc space narrowing (OR = 2.9 (95% CI 1.2 to 7.5)) and hip JSN (OR = 2.0 (1.0 to 4.2)). No consistent effects were seen for hand osteoarthritis. The associations remained after adjustment for age and body mass index. Conclusions: Progression of knee osteoarthritis is associated with progression of lumbar spine and hip osteoarthritis. This may have implications for trial methodology, the selection of patients for osteoarthritis research, and advice for patients on prognosis of osteoarthritis.